2013
DOI: 10.1111/ctr.12068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a collaborative chronic care approach to improve outcomes in kidney transplant recipients

Abstract: Several studies found that renal transplant recipients with chronic kidney disease have untreated complications and do not attain recommended clinical targets. Using a before/after design with propensity score-matched controls, we evaluated whether an advanced practice nurse-led interprofessional collaborative chronic care approach could improve clinical outcomes for CKD transplant patients compared with a traditional physician-led model. The intervention included strategies for disease self-management, shared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 25 publications
0
68
0
5
Order By: Relevance
“…Their findings showed that adherence to guidelines improved and, more importantly, that emergency room visits and hospital admissions decreased in the intervention group. 10 Similarly, a randomized controlled trial that examined the impact of a telemedicine-supported chronic care case management intervention showed that renal transplant recipients in the intervention group had significantly fewer unplanned admissions and shorter Table 1 Center and patient characteristics and average level of chronic illness management (PACIC). length of unplanned hospital stay compared to those in the standard care group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings showed that adherence to guidelines improved and, more importantly, that emergency room visits and hospital admissions decreased in the intervention group. 10 Similarly, a randomized controlled trial that examined the impact of a telemedicine-supported chronic care case management intervention showed that renal transplant recipients in the intervention group had significantly fewer unplanned admissions and shorter Table 1 Center and patient characteristics and average level of chronic illness management (PACIC). length of unplanned hospital stay compared to those in the standard care group.…”
Section: Discussionmentioning
confidence: 99%
“…5 Chronic illness management (CIM), a care model which emphasizes continuity of care and promotes self-management support for patients, could therefore provide an opportunity to improve long-term outcomes post HTx given promising results in other chronic patient populations. 5,8,9 Studies in non-HTx populations have shown that CIM is associated with decreased healthcare utilization, 10,11 improvements in health-related behaviors, 12 increased quality-of-life, 11 and greater patient and caregiver satisfaction. 12 In transplantation, the reengineering of transplant follow-up care according to the principles of CIM has resulted in improved clinical outcomes, reduced health care utilization, and reduced costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, em virtude do aumento da ingestão hídrica e do uso de diuréticos após o transplante, o transplantado interrompa o sono várias vezes durante a noite, em virtude da urgência urinária, o que contribui para o aparecimento dessa necessidade alterada (19,20) . Diante dessa necessidade alterada, o enfermeiro visando promover o sono e repouso adequado do paciente pode realizar intervenções como: ensinar ao cliente técnicas de relaxamento; determinar o efeito dos medicamentos sobre o sono; discutir com o paciente e a família as medidas de conforto, técnicas de monitoramento do sono e as mudanças no estilo de vida e oferecer ambiente calmo e agradável para o descanso adequado (17,18) .…”
Section: Introductionunclassified
“…Algumas atividades de lazer e recreação podem promover mais conforto para os clientes, assim como favorecer a manutenção de relacionamento interpessoal e afastamento da solidão (17) . Dessa forma, o enfermeiro deve desenvolver atividades relaxantes e de lazer compatíveis com a sua condição clínica do paciente, bem como rever a história de atividades/passatempos prediletos e possíveis modificações (19,20) . As necessidades humanas básicas alteradas listadas anteriormente são relevantes, visto que englobam quase todos os pacientes renais crônicos no pós-transplante renal.…”
Section: Introductionunclassified